Dynamic Phosphoproteome Profiling of Zebrafish Embryonic Fibroblasts during Cold Acclimation. Issue 2 (8th January 2020) - Yan, Junjun; Long, Yong; Zhou, Tong; Ren, Jing; Li, Qing; Song, Guili; Cui, Zongbin
Abstract: Temperature affects almost all aspects of the fish life. To cope with low temperature, fish have evolved the ability of cold acclimation for survival. However, intracellular signaling events underlying cold acclimation in fish remain largely unknown. Here, the formation of cold acclimation in zebrafish embryonic fibroblasts (ZF4) is monitored and the phosphorylation events during the process are investigated through a large‐scale quantitative phosphoproteomic approach. In total, 11 474 phosphorylation sites are identified on 4066 proteins and quantified 5772 phosphosites on 2519 proteins. Serine, threonine, and tyrosine (Ser/Thr/Tyr) phosphorylation accounted for 85.5%, 13.3%, and 1.2% of total phosphosites, respectively. Among all phosphosites, 702 phosphosites on 510 proteins show differential regulation during cold acclimation of ZF4 cells. These phosphosites are divided into six clusters according to their dynamic changes during cold exposure. Kinase–substrate prediction reveals that mitogen‐activated protein kinase (MAPK) among the kinase groups is predominantly responsible for phosphorylation of these phosphosites. The differentially regulated phosphoproteins are functionally associated with various cellular processes such as regulation of actin cytoskeleton and MAPK signaling pathway. These data enrich the database of protein phosphorylation sites in zebrafish and provide key clues for the elucidation of intracellular signaling networks during cold acclimation of fish.